Hindi-Urdu : sajha sanskriti - Simha, Murali Manohar Prasad (Neśanal Buk Trast, Indiya, 2010)
Comparative study of Hindi and Urdu languages and literatures; traces the influence, common elements, and history of both; contributed articles